Penguatan Literasi Sains Melalui Permainan Edukatif Pada Siswa Kelas VI SDN 37 Kendo Kota Bima - Mei Indra Jayanti; Nurfathurrahmah Nurfathurrahmah; Ariyansyah Ariyansyah; Erni Suryani (Rengganis Jurnal Pengabdian Masyarakat, 2022)
The results of the 2018 PISA study, the scientific literacy of students in Indonesia are still low at rank 70 out of 79 countries and the low level of scientific literacy skills in elementary schools, this underlies the dedication to develop scientific literacy through educational games at one of the elementary schools in Bima city. namely the VI grade students of SDN 37 Kendo, Bima City. The activity was carried out using the action research method using a word game approach involving students as the subject of the activity. Before the start of the game, it begins with ice breaking and then an introduction is given in the form of an introduction to the scientific names of animals and plants that students often find in their daily environment. The activity was continued by giving a guessing game of animal names and plant names. At the end of the activity, an evaluation was carried out by asking questions about the material that had been studied and asking several students to provide responses or responses related to the activities on that day. The results showed that 11 out of 12 students had correctly guessed the names of animals and plants that were often found around them based on the keywords mentioned by us. It can be concluded that community service activities for elementary school students with the theme of strengthening scientific literacy through educational games have a positive impact on increasing students' scientific literacy.